Contemporary Aristotelian metaphysics - Tahko, Tuomas E. 1982- (Cambridge University Press, 2012)
Aristotelian (or neo-Aristotelian) metaphysics is currently undergoing something of a renaissance. This volume brings together fourteen essays from leading philosophers who are sympathetic to this conception of metaphysics, which takes its cue from the idea that metaphysics is the first philosophy. The primary input from Aristotle is methodological, but many themes familiar from his metaphysics will be discussed, including ontological categories, the role and interpretation of the existential quantifier, essence, substance, natural kinds, powers, potential, and the development of life. The volume mounts a strong challenge to the type of ontological deflationism which has recently gained a strong foothold in analytic metaphysics. It will be a useful resource for scholars and advanced students who are interested in the foundations and development of philosophy